Pengaruh Variasi Diameter Disc Brake dan Tekanan Master Silinder terhadap Performa Pengereman Sepeda Motor 110 cc - Sulton Nasrullah; Purwoko Purwoko; Muhammad Akhlis Rizza; Sugeng Hadi Susilo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Braking performance is an important aspect of motorcycle safety because it relates to the vehicle’s ability to reduce speed and stop properly. In a hydraulic disc brake system, braking is influenced by mechanical and hydraulic factors, especially disc brake diameter and master cylinder pressure. Disc brake diameter determines the effective braking radius, while master cylinder pressure generates hydraulic pressure that is transmitted to the caliper. This study aims to analyze the effect of disc brake diameter and master cylinder pressure variations on the braking distance and braking time of a 110 cc motorcycle. This research used a quantitative experimental method with a Honda Revo Injection 110 cc motorcycle as the test object. The disc brake diameter variations were 190 mm, 220 mm, and 260 mm, while the master cylinder pressures were 2 bar, 4 bar, and 6 bar. Each treatment combination was tested three times at an initial speed of 40 km/h on a dry and flat asphalt road. Braking distance was obtained from front wheel rotation data recorded by a magnetic digital counter, while braking time was determined from video recordings. The data were analyzed using Two-Way ANOVA and response optimization. The results showed that increasing disc brake diameter and master cylinder pressure reduced braking distance and braking time. The best combination was obtained at a 260 mm disc brake diameter and 6 bar master cylinder pressure, producing a braking distance of 12.8 m and a braking time of 2.3 s.